Medication-Related Osteonecrosis of the Jaw Treated by Ozonized Oil: A Case Report - Saldanha, Mariana Pinheiro; de-Moura, Beatriz Fernandes; Lins, Renata Ximenes; Venturi, Beatriz da Rocha Miranda; Freire, Nathalia de Almeida; Israel, Mônica Simões (Journal of Oral Diagnosis, 2020)
Ozone is an atmospheric gas well-known for its excellent medicinal properties, including antimicrobial activity, immunostimulant and antioxidative. Ozone therapy has been used in dental medicine for treatment of herpetic infection, periodontitis, endodontic infec- tion, acute abscesses and medication-related osteonecrosis of the jaw. This study aims to report the protocol and results of the local use of ozonized oil in the management of patient with medication-related osteonecrosis of the jaw. 81-year-old white female, with exposed bone in the jaw, on left side, and a history of sodium alendronate used to treat osteoporosis. The treatment consisted of ozone therapy with ozonized oil, according to the following protocol: previous mouthwash chlorhexidine 0.12%, Periogard®, for one minute; local application of ozonized oil, Philozon®, with a 5ml syringe no needle, for 10 minutes, re-appliance every two minutes; 10 sessions, once a week each. Between the eighth and ninth treatment week, we observed spontaneous bone sequestration and after six months of follow up, we found local tissue regeneration.